Efektivitas Produk Simplisia Pestisida Nabati Terhadap Pertumbuhan Tanaman Pakcoy (Brassica rapa L.): Effectiveness of Vegetable Pesticide Simplicia Products on Pakcoy (Brassica rapa L.) Plant Growth - Widya, Surya Ari; Inti, Ristani Widya (Journal of Applied Plant Technology, 2022)
The obstacles faced in increasing and stabilizing the production of pakcoy Brassica rapa L. one of them is due to pest attacks. The main pests that attack pakcoy plants are Plutella xylostella L., C. pavonana, earthworms (Agrotis ipsilon), and grayworm (Spodoptera litura). The use of pesticides can provide the only form of crop protection available Developing countries from some pesticides that have been banned from use in the European Union (EU), as they have recognized the harmful properties of such pesticides. Vegetable pesticides are effective against various destructive pests and diseases. Broadly speaking, vegetable pesticide raw materials are easy to obtain, cheap, easily accessible, quickly decompose, and have little toxicity to receiving agents. Simplisia vegetable pesticide product is a pesticide product based on soursop leaves, lemongrass, and papaya leaves. All three ingredients contain chemical compounds or extractive substances. This study used vegetable pesticide simplicia products with several concentrations to suppress the attack of pakcoy leaf-destroying pests. The research took place in the experimental garden was carried out for 4 weeks from the seeding period to harvest. Research is carried out by experimental methods. The results of this study show that vegetable pesticide simplicia is able to suppress the attack of pakcoy leaf pests with a very significant concentration found in the P2 treatment, which is 40grams per liter of water